Phytonutritional Composition and Antioxidant Properties of Southern African, Purple-Fleshed Sweet Potato (Ipomoea batatas (L.) Lam.) Storage Roots - Ayanda Ngcobo; Sephora Mutombo Mianda; Faith Seke; Laurie M. Sunette; Dharini Sivakumar (MDPI AG, 2024)
Purple sweet potatoes (Ipomoea batatas (L.) genotype) in Southern Africa have a phytonutritional composition and antioxidant properties that can increase incomes and improve nutrition. This study compared the phytonutrient composition and antioxidant properties of four purple-colour sweet potato genotypes (local Purple-purple, '2019-1-1', and USA genotypes, '08-21P' and '16-283P'). These purple sweet potato genotypes were characterised by UPLC/QTOF/MS and 16 phenolic compounds were identified. Purple-purple (very dark purple) showed the highest concentration of cyanidins and peonidin derivatives. Chlorogenic acid derivatives were highest in the genotype '16-283P'. 'Puple-purple' and '16-283P' displayed the strongest antioxidant power and scavenging activities. Diaffeoylquinic acid isomer 1 was identified as the marker candidate for distinguishing the four purple sweet potato genotypes. Southern Africa's highest-protein sweet potato genotypes are Purple-purple (28.81 g/100 g) and '08-21 P' (24.31 g/100 g). A 13.65 g portion of '2019-1-1' would meet the Recommended Dietary Allowance (RDA) for iron for men, while 25.59 g would meet the RDA for children, and 30.72 g would meet the RDA for women. The sweet potato root of genotype '2019-1-1' provides 31.43 g of Zn per day for children and 22.86 g for adults. The roots of local cultivar Purple-purple can be used as functional food ingredients.